Pemikiran Pendidikan A. Malik Fadjar - Kamal, Hikmat; Nata, Abuddin (Ta'dibuna: Jurnal Pendidikan Islam, 2017)
The formulations of the problems of this research are: how does the educational pattern of thinking of A. Malik Fadjar? What are the indicators of educational thinking of A. Malik Fadjar? What do the factors contribute to the educational thinking of A. Malik Fadjar? And how is the relevance of educational thinking of A. Malik Fadjar with educational praxis? The aims of this research are to reveal and to find the educational thinking/ideas of A. Malik Fadjar. This research employed a qualitative design by investigating data from the writing of A. Malik Fadjar and others’ original writing about A. Malik Fadjar. The data collected is then described holistically, comprehensively, and systematically, which is then analyzed by social history approach of Islamic educational thinking, i.e. an approach observing background of the emergence of the thinking with factors affecting it and the relevance of the thinking for the present and future time to locate conceptual and substantive ideas and thinking. The research concludes that A. Malik Fadjar has a modern-religious pattern of thinking. Modern, because his thinking is oriented to the present and future time, always accepts the changes, open-minded, innovative and progressive. Religious, because of his family background, education, and also his organization culture are based on Islamic values. His pattern of thinking is shown by his vision, mission, and aims of education, curriculum, human resources, institution, and educational management. This thinking is emerged affected by both internal and external factors. From internal, the factors affected his thinking are educational background, personality and family. While from external, the factors are environment, job position, and socio-political situation in his era. Lastly, educational thinking of A. Malik Fadjar is still relevant to apply to the present and future time. Keywords: A. Malik Fajar, education concept, Islamic education